The made-up self : impersonation in the personal essay - Klaus, Carl H. (University of Iowa Press, 2010)
In this first book-length study of the personal essay, Carl Klaus unpacks the writer's made-up self and the manifold ways in which a wide range of essayists and essay have brought it to life. By reconceiving the most fundamental aspect of the personal essay--the I of the essayist--Klaus demonstrates that this seemingly uncontrived form of writing is inherently problematic, not wilfully devious but bordering upon the world of fiction. He develops this key idea by explaining how structure, style, and voice determine the nature of a persona and our perception of it in the works of such essayist.